The role of students' and parents' emotional intelligence in academic self-efficacy - Nur Rafidah, Othman; Chee Siong, Teh (UNIMAS Publisher, 2025)
Academic self-efficacy (ASE) is an important determinant of academic success, influencing students’ motivation, resilience, and performance. Previous research has consistently demonstrated a positive association between emotional intelligence (EQ) and ASE. However, most studies have assessed either students’ or parents’ EQ separately, limiting understanding of their combined impact, particularly in the context of university students. This gap restricts insight into how both individual and familial emotional factors shape academic confidence. The present study investigated the effects of students’ and parents’ EQ on ASE among 230 university students. Correlation analyses revealed a strong positive relationship between students’ EQ and ASE. Parents’ EQ also correlated positively with ASE, although the association was weaker. Regression analysis confirmed that students’ EQ was a stronger predictor of ASE compared to parents’ EQ. Notably, some students displayed high ASE despite lower parental EQ, indicating the importance of resilience and additional contributing factors to academic achievement. These findings emphasize the value of strengthening both student and parental EQ to enhance academic performance and emotional well-being. Further research should examine other psychological and contextual factors influencing university students’ success and developmental outcomes.